Descarte e destinação dos caroços de açaí em Macapá e Santana no estado do Amapá - MIRANDA, Lidiane de Vilhena Amanajás (2018)
The intensification of the production and consumption of açaí pulp led to the generation of large amounts of residue biomass of açaí. Considering the increase in the quantity of this organic residue, it is important that more and more solutions are sought for their use. This study aimed to identify the discard and destination of açaí seeds in the municipalities of Macapá and Santana. We choose the method of modeling species distribution. 212 Artisan açaí batsman were interviewed in the period between May and July 2017, with application of semi structured forms for 151 artisan açaí batsman in Macapá and 61 artisan açaí batsman in Santana. The data analysis was performed with the aid of the application of the tests in the free program R. With the use of an integrated set of Geographic Information System software, ArcGIS, the information on the way of discarding and the destination of açaí seeds, was spatialized in an urban cartographic base of Macapá and Santana. The results of the açaí berry activity are mostly performed (77%) by men, with an adult age group, and low level of education (3% illiterate, 20% elementary education and 34% elementary education II) and maintaining a family intergenerationality. Estimate a daily amount of 11,580 kg of seeds açaí lumber destined for potteries, and 65% of the açaí batsman paying for the collection of açaí from their establishments. Thus, the way of discarding the açaí from the inside out of the seats is not determined by the size of "processing machine" batsman (small medium or large). The creation of collection points for accommodate is presented as an environmental measure standardization of the way the açaí batsman are to be adopted, thus ensuring the safety and efficiency of the collection service.